Ocean Acidification studies in the Baia di Levante (Vulcano island, Italy). Advantages and disadvantages of the “in situ” approach. - BOATTA, Fulvio (Università degli Studi di Palermo, 2014)
Years of scientific research have shown that acidification of oceans (OA) is an undisputed fact. Why is it so important to increase knowledge about OA? Because many animals and plants in the ocean have calcium carbonate skeletons or shells, and a decreasing in pH can affect their population health state and the marine-ecosystem structure. Another point of view about OA which must to be considered is that it may alter the behavior of sediment-bound metals, modifying their bioavailability and thus toxicity. The toxic free-ion concentration of metals such as copper may increase by as much as 115% in coastal waters in the next 100 years due to reduced pH. Since increasing atmospheric CO2 over the next 200 years will cause a pH decrease in ocean water, and consequently change the organic and inorganic speciation of metals in surface ocean waters, and it will effect on their interaction with marine species. Most of the intense submersed hydrothermal seeps are located near the isthmus of the Baia di Levante along the beach (38°25’01.44”N, 14°57’36.29”E), where dispersed underwater leaks cover a 130 × 35m shallow water area (<1m depth). Here we aim at studying the geochemical characteristics of seawater in the Baia di Levante area. We studied the most prominent geochemical parameters across the whole bay and focused on the spatio-temporal variability of pH/CO2 along a stretch of coast in the northeastern part of the bay in the Vulcanello area. Eh and pH were greatly affected by the main vents. Eh values range from -152 to 170 mV in April and from -23 to 171 mV in September 2011 and from -39.7 to 181.3 in May 2012, while pH values range between 5.70 and 8.05 in April and from 6.05 to 8.03 in September 2011 and from 5.85 to 8.03 in May 2012. These is the reason why a pH and Eh gradient (from bubbles to offshore) affect seawater chemistry and biota in the Bay. About 3.6 tonnes of CO2 bubble into Baia di Levante per day which strongly influences the seawater chemistry of the area. The pH displayed a clear gradient from ...